Community nudges: why we need tools for turning on the we-mode to tackle problems that concern all of us - Denise de Ridder (Humanities & Social Sciences Communications)
Abstract Nudges are behavioral interventions to subtly steer citizen choices by making desirable options easier or more attractive. More than 15 years of research and practice have revealed that such gentle encouragements are effective policy instruments in directing personal decisions without violating the principles of good governance. However, with a focus on individual behavior, there has been less attention to nudges as a policy device for promoting decisions that are good for all of us and tackle societal challenges that require collective effort. In the present review, I address this knowledge gap by introducing the novel concept of community nudges. I discuss a new outlook that seeks to understand how nudges may support communities in making decisions to shape desirable outcomes for the benefit of all. I suggest two avenues for designing community nudges that support people in committing to a common cause. One way is the creation of nudges that call for considering other people’s concerns by speaking to their ability to empathize. Another way is to facilitate people to act together as a group to contribute to a common cause, resonating with recent calls for collective action in addressing critical societal problems. I present initial evidence that community nudges have the potential to increase collective commitment by avoiding an excessive focus on individual responsibility for problems that demand collaborative action. In the final section, I describe the opportunities and challenges for the implementation of community nudges in public policy by connecting the emerging evidence on community nudges with the literature on collaborative governance as an alternative for attempts to secure acceptance of top-down generated solutions for important problems that affect us all.